2021
DOI: 10.1002/joc.7433
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impact on sea surface winds in Southeast Asia

Abstract: Numerical representation and climate projections of sea surface winds over Southeast Asia (SEA) are assessed here using an ensemble of the Coupled Model Intercomparison Project Phase 5 (CMIP5) downscaled simulations performed over the 20th and 21st centuries under Representative Concentration Pathways (RCPs) 4.5 and 8.5 scenarios within the Coordinated Regional Climate Downscaling EXperiment (CORDEX)‐SEA project. The ensemble is based on two regional climate models (RCMs: RegCM4 and RCA4), and CMIP5 simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Second, Ekman pumping-induced upwelling (OFU hereafter) develops offshore in the area of strong positive wind and surface current vorticity (Liu et al, 2012;Da et al, 2019;Ngo and Hsin, 2021). Third, recent studies have revealed that coastal upwelling (NCU hereafter) can develop along the northern part of the central Vietnamese coast (Da et al, 2019;Ngo and Hsin, 2021;To Duy et al, 2022). Last, To Duy et al (2022) showed for the first time that upwelling develops off the Mekong Delta in the wake of Con Dao islands (see Fig.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Second, Ekman pumping-induced upwelling (OFU hereafter) develops offshore in the area of strong positive wind and surface current vorticity (Liu et al, 2012;Da et al, 2019;Ngo and Hsin, 2021). Third, recent studies have revealed that coastal upwelling (NCU hereafter) can develop along the northern part of the central Vietnamese coast (Da et al, 2019;Ngo and Hsin, 2021;To Duy et al, 2022). Last, To Duy et al (2022) showed for the first time that upwelling develops off the Mekong Delta in the wake of Con Dao islands (see Fig.…”
Section: Introductionmentioning
confidence: 97%
“…The interannual variability of the SVU has been investigated in numerous previous studies. In the SCU, OFU and MKU regions, the interannual variability of summer wind intensity is related to and in phase with the intensity of the summer monsoon, and is the main driver of the interannual variability of upwelling intensity (Wang et al, 2006;Chen et al, 2014;Li et al, 2014;Da et al, 2019;Ngo and Hsin, 2021;To Duy et al, 2022). ENSO (El Niño Southern Oscillation) also impacts the upwelling in those regions, due to its influence on summer monsoon wind (Wang et al, 2006;Kuo et al, 2004;Loick-Wilde et al, 2017;Da et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ocean circulation in the South China Sea (SCS), one of the largest semi-enclosed seas in the world (Fig. 1), is under the influence of several factors of variability at different scales: typhoons, seasonal monsoon, interannual to decadal variability, and climate change (Wyrtki, 1961;Herrmann et al, 2020Herrmann et al, , 2021. The SCS is moreover impacted by human activities, with highly densely populated coastal areas (Center for International Earth Science Information Network -CIESIN -Columbia University, 2018), which generate problems such as marine pollution (release of industrial, agricultural or domestic contaminants, such as pharmaceuticals, pesticides, heavy metals, or plastics).…”
Section: Introductionmentioning
confidence: 99%